A Case Study on Personal Problems of Ninth Grade Students at SMPK Adisucipto Kupang - Lansiana Muna; Wens Nagul (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
This study aims to describe the impact of parental divorce on the academic performance of a ninth-grade student at SMPK Adisucipto Kupang. The research subject, referred to as LL, is a 14-year-old adolescent who has lived in an incomplete family structure since before birth. His mother works in Malaysia, while LL lives with relatives and experiences both physical and emotional pressure. This research employed a qualitative approach with a descriptive method, collecting data through observation, interviews, and documentation. The informants included the homeroom teacher, guidance and counseling teacher, subject teachers, and LL’s close friend. The findings indicate that parental divorce significantlSy affects LL’s emotional condition, characterized by sadness, withdrawal, low motivation, and difficulty concentrating. These emotional challenges directly influence LL’s academic performance, which shows a noticeable decline, with most subjects not meeting the minimum competency standards. This study highlights the importance of emotional support and appropriate guidance to help students affected by parental divorce adapt and improve their learning outcomes.